George's Marvellous Medicine - Roald Dahl (Puffin Books London, United Kingdom, 2011)
George's Marvellous Medicine is one of Roald Dahl's most brilliant tales of naughtiness. ***Find Quentin Blake's illustrious illustrations in full-colour for this wonderful 30th anniversary edition***Most grandmas are kind and helpful ladies. Not George's grandma. She's a grumpy and grizzly old grouch and George wants to teach her a lesson. So when it's time for her medicine, George concocts a bubbling, frothing, marvelous mixture, which is guaranteed to send her through the roof . . . "A true genius . . . Roald Dahl is my hero" David Walliams ***with an exciting look into Roald Dahl's world***Roald Dahl, the best-loved of children's writers, was born in Wales of Norwegian parents. After school in England he went to work for Shell in Africa. He began to write after "a monumental bash on the head", sustained as an RAF pilot in World War II. Roald Dahl died in 1990.Quentin Blake is one of the best-known and best-loved children's illustrators and it's impossible now to think of Roald Dahl's writings without imagining Quentin Blake's illustrations.
Keywords: Humorous Fiction + Fantasy -- Humorous Fiction + Fantasy